PENELITIAN EKOLOGI HUT AN LAHAN PAMAH DI BARITO ULU, KALIMANTAN TENGAH: II. SERASAH DAN KANDUNGAN HARANYA [Ecological Studies of Lowland Forest in Barito Ulu, Central Kalimantan: II. Litterfall and Nutritional Content] - Mirmanto, Edi (Research Center for Biology-Indonesian Institute of Sciences, 1999)
A study on litterfall and their nutrient content has been conducted in the Barito Ulu research station, Central Kalimantan. Five plots of 50m x 50m were established to describe the forest structure and floristic composition. In each plot 10 of 1m x 1m litter-traps were emplaced on 25-28 April 1994, and litterfaii (ieaves, branches, flowers+fruits and miscellaneous) was collected twice at the mid and the end of month from May 1994 until May 1995. The litterfall chemical analyses were made for sampbs collected in May, June, July 1994 (dry season) and November and December 1994 and January 1995 (wet season). The mean annual total litterfall in the five plots was 8,4 t ha yr< (range 7,3-9,5). The total litterfall was highest in October 1994 coinciding with the later part of dry season. The litterfall mineral-element concentrations and accession were below or within the range reported for other tropical forests. On the basis of Vitousek litter nutrient concentration hypothesis phosphorus tended to be more efficiently used than nitrogen. This means that growth of forest would be expected to be more limited by phosphorus. However the results of fertilization experiment in this forest suggested that primary production of forest might be more limited by nitrogen. This is a new information that primary production of lowland tropical forest was also limited by nitrogen. The results in detail of the fertilization experiment will be published separately.